The need for thoracic surgery in adult patients receiving extracorporeal membrane oxygenation: a 16-year experience. (July 2013) - Joshi, V; Harvey, C; Nakas, A; Waller, DA; Peek, GJ; Firmin, R
Objectives: Patients on extracorporeal membrane oxygenation (ECMO) are at risk from thoracic complications such as bleeding or pneumothorax, which may subsequently necessitate thoracic surgical intervention. We aimed to: 1) analyse the indication and nature of thoracic surgical intervention in these patients and 2) analyse the effect of a change in the ECMO circuit from roller pump to centrifugal pump on transfusion requirements pre and post thoracotomy. Methods: We retrospectively reviewed a prospectively collected database of 569 adults put on ECMO between 1995 and 2011. Patients undergoing thoracotomy were identified and outcomes were statistically analysed. Results: Forty thoracotomies were performed in 18 patients [61% male, median age 31 (14-56) years, one bilateral procedure]. The indications for ECMO included: pneumonia 14/18 (78%), trauma 2/18 (11%) and other 2/18 (11%). Median duration on ECMO was 13 (1–257) days and the time to initial thoracotomy was 10 (1-183) days. The indications for thoracotomy were: excessive bleeding post chest drain insertion (11/19, 58%), uncontrolled air leak (9/19, 47%) and pleural effusion (4/19, 21%). The primary operations were 12/19 (63%) evacuation of haemothorax, 3/19 (16%) lung repair, 2/19 (11%) diagnostic lung biopsy and 2/19 (11%) other. Ten patients needed a further 21 thoracotomies (3 lobectomies); average 2 (1-5) per patient. In total, 30/40 (75%) thoracotomies were performed for bleeding complication. The change from roller to centrifugal pump trended towards a reduction in mean transfusion requirements in these patients following thoracotomy (11.5 versus 4 units, p=0.14). The in-hospital mortality was 7/18 (39%) patients. There were no statistically significant predictors of poor outcome. Conclusions: The need for thoracotomy whilst on ECMO is 3.2% in this large series. Intervention may be complicated, thus, either ECMO specialists should have thoracic training or thoracic surgeons should be on-site. Potential mortality is high and, although not statistically significant, a difference in transfusion requirements was observed following the change of circuit.